Analytical Approach for modelling of Heat generation in low-speed friction riveting of polymer/Aluminium joints. (2021) - N.J., Vignesh; N., Rajesh Jesudoss Hynes; P., Shenbaga Velu
Abstract: Developments in the field of joining technologies have given researchers increased opportunities for joining dissimilar materials in so many areas such as automotive, aerospace, marine and structural fields. The fields said here require fuel efficiency and at the same time improved mechanical and thermal properties. To achieve these, it is not sufficient for us to use olden day mono-material structures such as aluminium for the entire structures. Nowadays, improvements in polymers and composites have led to a very good foundation stone for using dissimilar materials as per requirements in the above-said fields. These polymers and composites are having very less weight and at the same time good strength as compared to some of the high strength metals. One of the significant properties of these materials is that they could be tailor-made as per requirements. Even though with these improvements in these polymers and composites, the methodology used for joining them with the metallic structures still becomes a challenging task. This present work details an account of the new technique namely Low-Speed Friction Riveting which is used for joining polymers and metals as a promising methodology. Here, the effect of temperature distribution on the point of contact of the two surfaces namely, the polymer and metal has been discussed. In the present work, the formulation of modelling approaches as well as the very fundamental pure thermal models are presented and discussed together with selected modelling results including prediction of heat generation with the thermo-mechanical model. Measurements by the IR sensor at the joint interface shows and reveal a reasonable agreement between the experimental results and the numerical calculations.